2014
DOI: 10.4236/ajac.2014.51002
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Laundry Water Characterisation

Abstract: Surfactants are the major active ingredients of laundry detergents. Therefore, special attention should be focused on the treatment and disposal of laundry wastewater. The aim of this study was to characterise the wastewater from a commercial laundry over 30 days. Physicochemical analyses were performed, monitoring the content of nitrogen, phosphate, heavy metals, linear alkylbenzene sulphonate (LAS), volatile organic acids and alcohols. The pH was approximately 5.6 and the COD approximately 4800 mg•L −1. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
3
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(76 citation statements)
references
References 40 publications
(60 reference statements)
5
54
3
6
Order By: Relevance
“…aesthetic losses due to the foam which can also cause adverse effects on ecosystems and biodiversity [1,2]. Detergents compounds in the laundry wastewater are biodegradable compounds and they have a short persistence time in the environment.…”
mentioning
confidence: 99%
“…aesthetic losses due to the foam which can also cause adverse effects on ecosystems and biodiversity [1,2]. Detergents compounds in the laundry wastewater are biodegradable compounds and they have a short persistence time in the environment.…”
mentioning
confidence: 99%
“…In addition, the optimization of strategies for removing LAS from laundry wastewater warrants research attention. This type of wastewater has one of the highest concentrations of LAS, reaching 1024 mg L -1 [3].…”
Section: Introductionmentioning
confidence: 99%
“…Surfactants may be toxic to the organism in soil or water (4). A study from Braga and Varesche (4) showed that LAS concentration in specific laundry wastewater is 163.65 mg/L. LAS concentration contributes to the presence of phosphorus.…”
Section: The Domestic Wastewater Characteristicsmentioning
confidence: 99%
“…In another side, the investment by local government in sanitation service or infrastructure remains low, including wastewater treatment provision (3,4). Even today, domestic wastewater is still disposed to drainage, river, or lake without proper treatment before (4). Some of the problems caused by wastewater, such as eutrophication, increasing treatment cost, decreasing the recreational value of water, health risks to humans and livestock, loss of oxygen and undesirable changes in the aquatic ecosystem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation